SOCIALIZATION ON THE USE OF SOCIAL MEDIA AS AN EDUCATIONAL TOOL FOR PARENTS IN SUPPORTING CHILDREN'S EDUCATION AT HOME AFTER LEARNING AT PAUD SRIKANDI - Saputra, Windhi Tia; Nathanael, Garcia Krisnando; Sadjijo, Priyono; Hakim, Luqman; Reza, Fikri (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
Given the rapid development of gadgets in the digital era, they have become a double-edged sword, offering both positive and negative impacts. Children, as frequent users, often use gadgets mainly for playing games and searching for information on the internet, without understanding the risks, including exposure to harmful content like pornography. This community service program aims to educate parents at PAUD Srikandi on how to guide their children in using the internet wisely, helping them become more aware of negative content.Effective communication with children before giving them gadgets involves three key points: (1) Discuss the needs: Talk about why the child wants a gadget and access to the internet, and whether it’s necessary. (2) Discuss responsibilities: Ensure children understand that parents have the right to monitor how the gadget is used and check its content. Set clear consequences if the gadget or internet is misused. (3) Discuss the risks: Encourage children to talk to their parents about anything that makes them uncomfortable while using the gadget or internet.